On the Acquisition of Derivational Suffixes by Kuwaiti EFL Learners - Alotaibi, Maye A.; Alotaibi, Abdullah M. (European Scientific Journal, ESJ, 2017)
This study aims to test the extent to which 90 Kuwaiti EFL learners are aware of the correct use of derivational suffixes in English. It also identifies the mains reasons of the errors that Kuwaiti EFL learners may make. In addition, it investigates whether the English proficiency level of the participants plays a role in their answers on the test. To this end, the participants were tested twice in this study; a multiple-choice test was used to check their comprehension skills, whereas a fill-in the blank test was used to measure their ability to produce the correct derivational suffixes in English. Following data analysis, the results reveal that Kuwaiti EFL learners are fairly aware of the correct use of English derivational suffixes to a certain degree; the total mean on both tests (comprehension = 70% and production = 56%) is 63%. The participants obtained higher percentage of correct answers on the comprehension test (mean= 70%) compared to the production test (mean = 56%). Additionally, the t-test shows that the participants’ English proficiency level plays a central role in their comprehension and production of these suffixes. The performance of the Advanced Learners (ALs) (comprehension = 77% and production = 62%) is better than that of the Intermediate Learners (ILs) (comprehension = 64% and production = 48%) on the tests. In particular, there is a statistically significant difference between the answers of ALs and ILs on both tests. Regarding the types of error made by the participants, I argued that the most noticeable ones are due to: (1) the modification that non-neutral derivational suffixes cause when they are attached to the word (stems/roots); and (2) first language (L1) influence. Finally, the study concludes with some recommendations for further research.